Influencia de la inulina en el contenido graso del queso pasta hilada tipo mozzarella fresco y aromatizado - Moreno Peñafiel, Raquel Marianela (2017)
Inulin is used mainly to replace fat and reduce its caloric content, adding it with probiotic bacteria to cheese, it becomes a symbiotic food. The objective of this study was to evaluate the influence of inulin and heat treatment in fresh mozzarella-type spiced cheese flavored with Origanum vulgare (oregano) and Rosmarinus officinalis (rosemary) by assessing the physicochemical characteristics and the sensory evaluation of the product final. To denote the effect, a completely randomized design (DCA) with a factorial arrangement of A x B x C was used, where the factor A: three percentages of inulin (0%, 1% and 2%), the B factor: two types of aromatizers (oregano and rosemary) and Factor C: Conditioning of the raw material (pasteurized and unpasteurized), with two repetitions, which corresponds to 24 experimental units. The data were analyzed with analysis of variance (ANOVA) and the means with the Tukey test at 5%. Through the statistical program StatGraphics and Infostat. The sensory characterization was carried out through a descriptive analysis and textural profile with a panel of semi-trained catadores. Inulin significantly influenced the pH, humidity, fat, protein and yield, highlighting the concentration of 1% inulin, flavored with oregano and made from unpasteurized milk in terms of choice by the tasters and physicochemical characteristics was the treatment 1% inulin with oregano, made from pasteurized milk. It is concluded that by incorporating a type of prebiotic food reduces its fat content turning it into a semi-fat cheese, which increases its moisture content and is considered a semi-hard cheese therefore increases its yield, denoting that a process subjected to a concentration of 1% Inulin maintains this characterization and does not affect its sensory characteristics (texture).